Pediatric Ovarian Torsion in a Medical Center in Taiwan: Case Analysis - Jun-Kai Kao; Chun-Chien Chiu; Po-Yu Wang; Meng-Kung Yu (Pediatrics and Neonatology)
Abdominal pain is one of the most common complaints made by patients visiting emergency departments; however, ovarian torsion is an uncommon cause of abdominal pain, especially in young children. Early diagnosis is essential in order to salvage the ovaries. We performed a retrospective analysis of patients under 18 years of age who visited Changhua Christian Hospital with adnexal torsion between June 2003 and June 2010. Methods: Medical records were reviewed for age, associated symptoms, past and present medical histories, physical findings, diagnostic tests performed, clinical course, pathological findings, and diagnoses. Results: A total of 21 patients were identified and included in the analysis; their mean (SD) age was 13.62 (3.75) years. Abdominal pain was the universal symptom. Vomiting or nausea was the second most common symptom (33.3%). The average period between symptom onset and diagnosis was 3.29 (6.39) days. Right-side adnexal torsion occurred in 14 patients, and left-side torsion in seven patients. Ovarian cysts, most often dermoid cysts (e.g., teratomas), were found in 16 patients (76%). Except for one conservatively treated case and one malignant case (adult granulose cell tumor), the other results of the pathological examination were as follows: eight dermoid cysts, two cystadenomas, one follicular cyst, and eight simple cysts. Conclusion: Although it is uncommon, adnexal torsion should be included in the differential diagnosis of lower abdominal pain in all girls, regardless of age. Sonography is helpful for making such a diagnosis. Time is a critical factor, and early laparoscopy or laparotomy may save a viable ovary.